The development of interactive multimedia edutainment software for dyslexic children (prototype) / Mohamad Izran Ibrahim - Ibrahim, Mohamad Izran (2005)
Multimedia elements are now widely used in many area of application such as business, medicine, marketing, military, education, and entertainment. So, this project aims to produce edutainment software using multimedia technology for learning and early reading. The group of user targeted to use this software is for the syndrome called Dyslexia. This project acts an early exposure to learning character and simple word. Researchers stated that children's cognitive developments begin in early stage in their life and suggested children's software should be designed suits to their needs. Therefore, this software will be the best supplement to the traditional teaching and learning method where children especially Dyslexic children, can help themselves in enhancing their ability in learning character and learning how to read. The beauty of this edutainment software is that not only provides entertainment to the user but also teaches the user how to remember the character, how to pronounce, how to spell a simple word. The children are also able to use the software at home without the supervision from a teacher since the software have an agent itself that act as a teacher. The methodology adopted to develop this software is System Development Life Cycle (SDLC) model. The software used for the development of this project are Macromedia Flash 5.0, Adobe Photoshop 7.0, Adobe Illustrator 10, Magix Music Maker 2005, Pocket Voice Recorder and Swish 1.51.